O ensino de física nos primeiros anos da educação básica: possibilidades lúdicas e experimentais - Curcio, Ana Laura [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
We discuss in the work the importance of experiential activities for Physics Teaching in the first years at Elementary Education. For this we start from the experience provided by the Teaching Project Initiation under Pibid CAPES, linked to the Department of Education from the Institute of Biosciences and activities of the Graduate Diploma in Physics Supervised, at Rio Claro Campus, São Paulo State, in partnership with Basic Education schools of the city. Based on some patterns and studies on the Teaching of Science in Elementary Education and particularly in the Ferreira’s work with Instrumentation for Physics Teaching, Electrostatic was chosen as base theme. We opted for the use of didactic experiments that provided in its construction the utilization of low cost materials, easy access and portability. Teaching strategies were aimed at inserting experiential activities during Elementary School I (first and third years of elementary school), intending to rescue the trial of Physics Education and Science for Basic Education. These experimental teaching activities were analyzed in this paper from the perspective of playfulness. We argue that experimentation with recreational attributes when properly used provides the interaction of individuals with the knowledge of Physical Sciences

Discutimos neste trabalho a importância das atividades experimentais para o Ensino de Física nos primeiros anos da Educação Básica. Para isso, partimos da experiência proporcionada pelo projeto de Iniciação a Docência, no âmbito PIBID CAPES, vinculado ao Departamento de Educação do Instituto de Biociências e das atividades da Graduação na Licenciatura em Física do Estágio Supervisionado, no Campus de Rio Claro, Estado de São Paulo, desenvolvidos em parceria com escolas da Educação Básica da cidade. Baseando-se em estudos sobre o Ensino de Ciências no Ensino Fundamental e, principalmente, nos trabalhos de Ferreira com Instrumentação para o Ensino de Física, na temática Eletrostática. Optou-se pela utilização de experimentos didáticos que proporcionassem em sua construção a utilização de materiais de baixo custo, fácil acesso e portabilidade. Foram estratégias didáticas visando a inserção de atividades experimentais durante o Ensino Fundamental I (primeiro e terceiro ano do Ensino Fundamental), pretendendo resgatar a experimentação do Ensino de Física e Ciências. Tais atividades didáticas experimentais foram analisadas neste trabalho sob o enfoque da ludicidade. Discutimos que a experimentação com atributos lúdicos quando devidamente utilizada proporciona a interação dos sujeitos com o conhecimento de Física e Ciências
Keywords: Física - Estudo e ensino; Ensino fundamental; Professores - Formação; Pratica de ensino